2003
DOI: 10.1046/j.1365-2850.2003.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Too tired to care? The psychological effects of working with trauma

Abstract: This quantitative and qualitative longitudinal study was designed to examine the effects on caregivers working therapeutically with seriously traumatized people. The participants were 13 healthcare workers seconded into a trauma and recovery team (TRT) set up to help those traumatized by the Omagh bombing on 15 August 1998. Quantitative data were collected using the Compassion Satisfaction/Fatigue Test and the Life Status Review Questionnaire. Qualitative data regarding positive and negative aspects of working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 15 publications
5
112
1
13
Order By: Relevance
“…Seeing patients improve has been cited by health care workers as one of the most rewarding aspects of their jobs [8], and the absence of this makes working with terminally ill patients particularly difficult. In fact, caring for dying patients has been linked to stress, burnout and professional grief [33] [42].…”
Section: Discussionmentioning
confidence: 99%
“…Seeing patients improve has been cited by health care workers as one of the most rewarding aspects of their jobs [8], and the absence of this makes working with terminally ill patients particularly difficult. In fact, caring for dying patients has been linked to stress, burnout and professional grief [33] [42].…”
Section: Discussionmentioning
confidence: 99%
“…Literature was found for compassion fatigue in Ireland (Collins & Long, 2003), Israel (Berger & Gelkopf, 2011), and New Zealand (Brankin, 2010). Brankin's article addressed the importance of compassion fatigue but did not conduct original research, which left two articles that identified compassion fatigue in the countries of study.…”
Section: Compassion Fatiguementioning
confidence: 99%
“…Emotional exhaustion (9) Depersonalization (5) Personal Accomplishment (8) Involvement ( Likewise, the role of negative qualities like self-sacrificing behavior and negligence of selfnurturing behavior still needs to be better understood (Sabo, 2011). Gaining knowledge on qualities that predispose or prevent CF will pave the way for effective interventions that help…”
Section: Maslach Burnout Inventory (Mbi)mentioning
confidence: 99%